Association between frequency of breakfast consumption and cardiometabolic risk in Peruvian university teachers, 2019–2020 - Saintila, Jacksaint; Baquedano-Santana, Laura E.; Calizaya-Milla, Yaquelin E.; Ramos-Vera, Cristian; Barrientos, Antonio Serpa; Carranza-Esteban, Renzo F. (Frontiers in Nutrition, 2023)
Background: Although the relationship between health status and dietary intake has been extensively studied in the general population, there is a lack of research that has specifically examined the association between frequency of breakfast consumption and cardiometabolic risk in university teachers. Objective: To determine the association between the frequency of breakfast consumption and cardiometabolic risk in university teachers. Methods: A cross-sectional study was conducted in 176 teachers from a private university located in the eastern region of Lima, Peru (Mage: 37.0 years; SD: 0.8, range: 24 to 59 years). The study was conducted during the period from December 2019 to February 2020. Information was collected on anthropometric and biochemical parameters and frequency of breakfast consumption. Multinomial logistic regression models were used to explore the association between frequency of breakfast with sociodemographic, anthropometric, and biochemical variables. Results: The highest prevalence of excess body weight (44.4%) was observed in those who consumed breakfast 0 to 2 days/week, but without statistical differences. Those who reported Lowdensity lipoprotein cholesterol (LDL-C) < 160 mg/dL were 77% less likely to fall into the 3-5 day/week breakfast frequency category than those who reported a regular frequency of breakfast (6 to 7 days/week) (Adjusted OR = 0.23, 95% CI 0.08 to 0.73; p < 0.05). In addition, teachers who reported a breakfast frequency of 3 to 5 days/week were 83% more likely to have a glucose concentration < 110mg/dL compared to those who consumed breakfast of 6 to 7 days/week (Adjusted OR = 0.17, 95% CI 0.04 to 0.75; p < 0.05). Conclusion: Skipping breakfast for an extended period of time can have detrimental effects on cardiometabolic health. Promoting the benefits of breakfast could be a health message of great public health interest.